Preparation, properties, and structures of the radical anions and dianions of azapentacenes - Ji, Lei; Hahn, Sebastian; Geyer, Florian Ludwig; Tverskoy, Olena; Han, Jie; Dreuw, Andreas; Bunz, Uwe H. F. (Journal of the American Chemical Society, 2017)
A series of diazapentacenes (5,14-diethynyldibenzo[b,i]phenazine, 6,13-diethynylnaphtho[2,3-b]phenazine) and tetraazapentacenes (7,12-diethynylbenzo[g]quinoxalino[2,3-b]quinoxaline, 6,13-diethynylquinoxalino[2,3-b]phenazine) were reduced to their radical anions and dianions, employing either potassium anthracenide or lithium naphthalenide in THF. The anionic species formed were investigated by UV-vis-NIR, fluorescence and EPR spectroscopy, spectroelectrochemistry, and quantum chemical calculations. Single crystal X-ray structures of three of their radical anions and of three of their dianions were obtained. In contrast to the acenes, the anions of the azapentacenes are persistent and, in some cases, even moderately stable toward air, and were characterized.